Exploring the business strategy of Malaysian exporting manufacturing firms - Hashim, Mohd Khairuddin; Hamdan, Oemar (IAIN Antasari, 2006)
Business strategy has attracted much attention in the literature over the years.Despite the increased knowledge and attention on business strategy, the literature review suggests few studies have attempted to examine business strategy in the context of Malaysian exporting manufacturing firms.The purpose of this study is to explore this issue.More specifically, this study empirically explore the business strategy as found in 160 of exporting manufacturing firms.The findings of the study provide empirical evidence that suggests the exporting manufacturing firms adopted the following business strategies; differentiation focus strategy, marketing differentiation strategy, product differentiation strategy, service differentiation strategy, and innovative differentiation strategy.